Submission of Guna Bhakti Credit at PT Bank BJB KCP Jalan Cagak Subang - Vionika, Cindy (PT. LITERASI SAINS NUSANTARA, 2023)
Bank bjb is a type of commercial bank engaged in the banking sector which carries out activities to collect funds and distribute funds. Whereas banking is a financial institution that is growing rapidly in Indonesia, one of the banking activities is credit, the management of which requires credit administration procedures. The focus of this research is how the procedure is carried out in the credit granting process. In addition, to find out how to implement the theory of credit administration procedures at the bank. This study shows that the KGB credit administration procedure is in conformity between theory regarding administrative procedures and practice, it is good according to the existing Standard Operating Procedure (SOP). The procedure for applying for credit includes 9 stages, namely submitting files, investigating loan files, interview I, On The Spot, Interview II, Credit decision, Signing of the Credit Agreement, Credit Realization, and channeling and withdrawing funds. The procedure makes it easy to process each credit application so that it makes it easier for consumers to apply for credit, the time period for consumers to realize faster credit can be completed within 2 days until disbursement. For credit application procedures there are problems that must be corrected.